2011
DOI: 10.1002/jmri.22635
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic enhancement during the hepatobiliary phase after gadoxetate disodium administration in patients with chronic liver disease: The role of laboratory factors

Abstract: Purpose: To identify factors influencing hepatobiliary phase (HBP) hepatic enhancement on gadoxetate disodium-enhanced MRI in patients with chronic liver disease (CLD). Materials and Methods:We retrospectively reviewed abdominal gadoxetate disodium-enhanced MRIs and medical records of patients with (n ¼ 97) and without (n ¼ 48) CLD. CLD subgroups were formed based on normal/ abnormal components of liver function tests (LFTs). Hepatic enhancement coefficients (HEKs) were calculated on MRI, and compared with LFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In patients with cirrhosis, the delay of contrast medium uptake and biliary excretion may affect imaging of gadoxetic acid disodium. However, there was a recent evidence that the HBP hepatic enhancement in chronic liver disease patients is similar to those with no chronic liver disease as long as direct bilirubin remains normal (44). Our results also showed that the accuracy of two subgroups with or without chronic liver disease only was almost the same.…”
Section: Discussionsupporting
confidence: 67%
“…In patients with cirrhosis, the delay of contrast medium uptake and biliary excretion may affect imaging of gadoxetic acid disodium. However, there was a recent evidence that the HBP hepatic enhancement in chronic liver disease patients is similar to those with no chronic liver disease as long as direct bilirubin remains normal (44). Our results also showed that the accuracy of two subgroups with or without chronic liver disease only was almost the same.…”
Section: Discussionsupporting
confidence: 67%
“…Chernyak et al [10] found that enhancement in the hepatobiliary phase was inversely correlated with model for end stage liver disease scores and the number of abnormal liver enzyme panels. Okada et al found that the ratio of liver/muscle enhancement was substantially higher in control groups and Child-Pugh A group compared to Child-Pugh B and C patients.…”
Section: Discussionmentioning
confidence: 98%
“…The signal intensity (SI) changes of liver after injection of gadoxetate have been investigated to determine correlation with grade of fibrosis [4,8,9], hepatic function [10][11][12] and outcome after liver-directed intervention [13][14][15]. However, such SI changes are dependent on extraneous factors including the injected dose, relative renal function, and the presence of hepatic steatosis [16][17][18].…”
mentioning
confidence: 99%
“…Thus, in compromised liver parenchyma (e.g. fibrotic or cirrhotic) the hepatobiliary phase may be delayed due to the reduced liver function [6,30,31]. For this reason, at our centre, whenever liver MRI is performed on patients with clinical suspicion of impaired liver function, a second imaging session with new patient positioning in the scanner is performed 40-50 min after the first examination.…”
Section: Discussionmentioning
confidence: 99%